Synthesis and characterization of transition metal (II) complexes of bidentate and tetradentate schiff base ligands - Mohd Zacaery, Khalik (Universiti Malaysia Sarawak (UNIMAS), 2008)
Two Schiff base ligands have been derived from the condensation reaction of 1,2-ethylenediamine with 2-acetylpyridine and benzophenone in 1:2 mole ratio, respectively. Five transition metal(II) {Co(II), Ni(II), Cu(II), Zn(II) and Cd(II)} complexes of 1,2-ethylenediamine-bis(2-acetylpyridine) ligand (1) have been synthesized by direct reaction of ligand (1) and transition metal(II) salts in 1:1 (metal:ligand) mole ratio in absolute ethanol. Another three transition metal(II) {Co(II), Cu(II) and Zn(II)} complexes of N,N’-bis(benzophenone)-1,2-diiminoethane ligand (2) have been synthesized by the procedure similar to ligand (1). Schiff base ligands (1-2) and their transition metal(II) complexes (3-10) have been characterized using elemental (CHN) analysis, UV-Visible and IR spectral studies. Among them, ligand (1) and its Zn(II) complex (6) have also been studied by 1H NMR spectra. All transition metal complexes are non electrolytic in nature. Spectral studies suggested that Schiff base ligand (1) acts as a neutral tretradentate (NNNN) chelating agent and Schiff base ligand (2) acts as a neutral bidentate (NN) chelating agent towards transition metal(II) ions.